The Role Of Religious Moderation In Countering Radicalism In The Village - Harsya, Rabith Madah Khulaili; Ridwan, Ahmad; Sa'diyah, Sa’diyah; Chatun, Sri; Susanto, Deny (Universitas Pahlawan Tuanku Tambusai, 2024)
This article comes from the author's service in the villages of Bulak and Bandar Baru for 1 month in these villages. This dedication began with the writer/devotee's sense of concern for villages that have great potential to be invaded by radicalism. This program is also a priority for BNPT and the Government of the Republic of Indonesia.